Left Ventricular End Diastolic Volume and Ejection Fraction Calculation: Correlation between Three Echocardiographic Methods - Nadia Benyounes; Clélie Van Der Vynckt; Thierry Tibi; Alexandra Iglesias; Olivier Gout; Sylvie Lang; Laurence Salomon (Cardiology Research and Practice)
Background. Left ventricular ejection fraction (LVEF) and end diastolic volume (EDV) are measured using Simpson’s biplane (SB), 3-dimensional method (3DE), and speckle tracking (STE). Comparisons between methods in routine practice are limited. Our purpose was to compare and to determine the correlations between these three methods in clinical setting. Methods. LVEF and EDV were measured by three methods in 474 consecutive patients and compared using multiple Bland–Altman (BA) plots. The correlations (R) between methods were calculated. Results. Median (IQR) LVEF_SB, LVEF_STE, and LVEF_3DE were 63.0% (60–69)%, 61% (57–65)%, and 62% (57–68)%. Median (IQR) EDV_SB, EDV_STE, and EDV_3DE were 85 ml (71–106) ml, 82 ml (69–100) ml, and 73 ml (59–89) ml. R between LVEF_SB and LVEF_3DE was 0.65 when echogenicity was good and 0.43 when poor. R for EDV_SB and EDV_3DE was 0.75 when echogenicity was good and 0.45 when poor. On BA analysis, biases were acceptable (<3.5% for LVEF) but limits of agreement (LOA) were large: 95% of the differences were between −15.4% and +18.8% for LVEF as evaluated by SB in comparison with 3DE, with a bias of 1.7%. In the comparison EDV_SB and EDV_3DE, the bias was 14 ml and the LOA were between −24 ml and +53 ml. On linear regressions, LVEF_3DE = 17.92 + 0.69 LVEF_SB and EDV_3DE = 18.94 + 0.63 EDV_SB. Conclusions. The three methods were feasible and led to acceptable bias but large LOA. Although these methods are not interchangeable, our results allow 3DE value prediction from SB, the most commonly used method.